Incipient colonies of the neotropical termite Cornitermes cumulans (Isoptera: Termitidae): comparing monogamy and polygamy as reproductive strategies - Da Silva, L. H.B.; Jost, C.; Vargo, E. L.; Costa-Leonardo, A. M. [UNESP]; Haifig, I. (Springer Nature, 2022)
A termite colony is generally founded by a monogamous pair of alates during swarming. However, primary polygyny resulting from pleometrotic associations has been recorded for some termites. These multiple queens may continue to be associated during colony lifespan or be dissociated by conflicts that result in colony fragmentation or death of some reproductives. To date, primary polygyny in the termite Cornitermes cumulans has occasionally been observed in the field but no records in the literature are available. Due to its irregular incidence, this study aimed to investigate the proximate factors involved in colony development and the rare occurrence of polygamous colonies of C. cumulans. Forty monogamous colonies and 20 polygamous colonies (10 polygynous colonies: two females and one male; 10 polyandrous colonies: one female and two males) were set up in the laboratory. The initial development was followed for a period of 100 days, during which time censuses of the colonies were performed. Polygynous colonies laid more eggs than monogamous ones, but not twice as many, as expected, until day 60. Conversely, monogamous colonies produced more larvae than polygynous colonies until the appearance of workers, when larvae started to molt to workers and decreased in number. Larvae were rarely observed in polygynous colonies, which may be associated with cannibalism of these individuals by one of the two females. Due to these factors, primary polygyny seems to be unlikely in C. cumulans during colony foundation, which is in accordance with observations of natural colonies that mostly contain only a single queen.
Keywords: Colony foundation; Eggs; Hatching; Higher termites; Reproduction